MEASURING RELIGIOUS FREEDOM IN INDONESIA: The Reconstruction of State’s Role, the Revitalisation of Faith’s Inclusiveness - Fawaizul Umam (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
This paper describes the challenges to nurture religious freedom in Indonesia due to the misrepresentation of the state’s roles. It discusses religious freedom based on the spirit of individual rights to practice religion (including not to embrace any religion). An analysis is started by proposing facts about the violence of religious freedom and some actual threats to religious freedom. Then, it is concluded with solution of two levels, namely reconstructing the relation between state and religion (public), and revitalizing the inclusiveness of religious pluralism in the people’s consciousness using Islam as its perspective. This is because religious freedom is still a great challenge for Indonesia both in the present and in the future. If we respond to the challenges wisely, the establishment and existence of religious freedom, peace, and inter-religious cooperation in this state is not impossible. Therefore, the prospect of religious freedom in Indonesia relies on the state’s and its citizens’ readiness to embrace the peaceful and tolerant values as the foundations to live in societies of multi-faiths groups.